Links Between Television Exposure and Toddler Dysregulation: Does Culture Matter? - Lecannelier-Acevedo, F (Elsevier Ltd, 2021)
Television exposure in early childhood has increased, with concerns raised regarding adverse effects on social-emotional development, and emerging self-regulation in particular. The present study addressed television exposure (i.e., amount of time watching TV) and its associations with toddler behavioral/emotional dysregulation, examining potential differences across 14 cultures. The sample consisted of an average of 60 toddlers from each of the 14 countries from the Joint Effort Toddler Temperament Consortium (JETTC; Gartstein & Putnam, 2018). Analyses were conducted relying on the multi-level modeling framework (MLM), accounting for between- and within-culture variability, and examining the extent to which TV exposure contributions were universal vs. variable across sites. Effects of time watching TV were evaluated in relation to temperament reactivity and regulation, as well as measures of emotional reactivity, attention difficulties, and aggression. Results indicated that more time spent watching TV was associated with higher ratings on Negative Emotionality, emotional reactivity, aggression, and attention problems, as well as lower levels of soothability. However, links between TV exposure and both attention problems and soothability varied significantly between cultures. Taken together, results demonstrate that increased time spent watching television was generally associated with dysregulation, although effects were not consistently uniform, but rather varied as a function of culturally-dependent contextual factors. © 2021 Elsevier Inc.